Pembimbingan “Basic English Speaking” di Tingkat Sekolah Madrasah Aliyah Key Lebu Witihama - Ummi Qalsum Arif (Pusat Riset dan Inovasi Nasional, 2025)
Speaking is one of the important skills in learning English. The success of learning English is also measured by speaking ability. However, this skill is still considered difficult to learn by students. The problem that is often faced in learning English is that students' ability to speak English is still low. This is caused by limited vocabulary and lack of understanding of the structure of the English language. Moreover, students who live in villages are still far from enthusiastic in learning English. To overcome this problem, lecturers conducted community service, especially at the MAS Key Lebu school with the topic of service, namely